PENGARUH PENDIDIKAN KESEHATAN METODE RICE TERHADAP KETERAMPILAN PERTOLONGAN PERTAMA CEDERA OLAHRAGA SPRAIN PADA PALANG MERAH REMAJA SMA NEGERI 1 JENGGAWAH: The Influence of Rice Method Health Education on First Aid Skills for Sprain Sports Injuries in Red Cross Teenagers at Senior High School 1 Jenggawah - Rodhistya Athoillah; Awatiful Azza; Mohammad Ali Hamid (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
A sprain or sprain is an injury to ligaments, namely the connective tissue that connects bones to bones in joints. By providing health education using the RICE method, it is hoped that teenage Red Cross members will be able to help themselves and others. The aim of this research is to determine the influence of RICE Method Health Education on First Aid Skills for Sprain Sports Injuries in Red Cross Teenagers at SMA Negeri 1 Jenggawah. This research uses a Pre-Experimental design with a One Group Pretest-Posttest approach. The research population consisted of 42 respondents and all of them were sampled using the Total Sampling technique. The hypothesis was tested using the Wilcoxon Test with α = 0.005. The research results showed that 36 respondents (85.7) had good skills, while 6 respondents (14.3) had sufficient skills. The p value obtained is 0.000, which means that H1 is accepted or there is an influence of the RICE method of health education on first aid skills for sprain sports injuries in the red cross youth at SMA Negeri 1 Jenggawah. The results of this research can be used as a reference to improve skills in a youth Red Cross organization.